Response of four evergreen savanna shrubs to an incidence of extreme drought: high embolism resistance, branch shedding and maintenance of nonstructural carbohydrates - Shen, Jing-Xian; Zhang, Yong-Jiang; Maenpuen, Phisamai; Zhang, Shu-Bin; Zhang, Lan; Yang, Lin; Tao, Lian-Bin; Yan, Peng-Yun; Zhang, Zhi-Ming; Li, Shu-Qiong; Yuan, Xia; Kongjarat, Wanwalee; et al. (Tree physiology, 2022)
Abstract Extreme drought events are becoming frequent globally, resulting in widespread plant mortality and forest dieback. Although savanna vegetation cover ~20% of the earth’s land area, their responses to extreme drought have been less studied than that of forests. Herein, we quantified branch dieback, individual mortality and the associated physiological responses of four evergreen shrubs (Tarenna depauperate Hutch., Maytenus esquirolii (H. Lév.) C.Y. Cheng, Murraya exotica L., Jasminum nudiflorum Lindl.) in a savanna ecosystem in Southwest China to an incidence of extreme drought during 2019 and 2020. We found that 80–100% of the individuals of these species exhibited branch dieback, whereas individual mortality was only found in T. depauperate (4.5%). All species showed high resistance to stem embolism (P50, water potential at 50% loss of hydraulic conductivity ranged from −5.62 to −8.6 MPa), whereas the stem minimum water potentials reached −7.6 to ca −10.0 MPa during the drought. The low water potential caused high native embolism levels (percentage loss of hydraulic conductivity (PLC) 23–65%) in terminal branches, and the remaining stems maintained 15–35% PLC at the end of the drought. Large within-individual variations in stem vulnerability to embolism were detected, and shedding of vulnerable branches could be a mechanism for shrubs to reduce water and carbon consumption. Overall, the content of total nonstructural carbohydrates (NSC) and their components in the stem were generally comparable to or higher than those in the rainy season in three of the four species. Because the leaves were turgor-less for most time during the drought, high NSC levels during the drought could be due to recycling of NSC from dead branches or translocation from roots. Our results suggest high tolerance of savanna shrub species to extreme drought, which could be facilitated by high embolism resistance in some stems and shedding of vulnerable branches to maintain individual water and carbon balance.